Development of a single mode narrow linewidth composite cavity fiber laser - Koh, Hui Lin. (2009)
In this project, the effectiveness of incorporating composite cavity technique into the design of an Erbium-doped fiber laser (EDFL) in achieving single mode narrow linewidth operation is being investigated. An all-fiber compound ring laser is formed by inserting a dual coupler fiber ring into the main cavity of an Erbium-doped fiber ring laser to act as a mode restrictive element. A reflective fiber bragg grating is also used as an internal cavity wavelength filter. This introduction of coupled cavity into the design of EDFL significantly reduces the number of longitudinal modes oscillating. The double ring EDFL is pumped with a 980nm laser diode and produces a laser emission at centre wavelength of ~1554.3nm.